Biomimetic glycopeptide hydrogel coated PCL/nHA scaffold for enhanced cranial bone regeneration via macrophage M2 polarization-induced osteo-immunomodulation. (June 2022) - Wang, Yaping; Wang, Jingrong; Gao, Rui; Liu, Xiang; Feng, Zujian; Zhang, Chuangnian; Huang, Pingsheng; Dong, Anjie; Kong, Deling; Wang, Weiwei
Abstract: The reconstruction of large cranial bone defects by bioactive materials without exogenous cells or growth factors remains a substantial clinical challenge. Here, synthetic fibrous glycopeptide hydrogel (GR gel ) self-assembled by β-sheet RADA16-grafted glucomannan was designed to mimic the glycoprotein composition and the fibrillar architecture of natural extracellular matrix (ECM), which was non-covalently composited with 3D-printed polycaprolactone/nano hydroxyapatite (PCL/nHA) scaffold for cranial bone regeneration. The glycopeptide hydrogel significantly promoted the proliferation, osteogenic differentiation of bone mesenchymal stem cells (BMSCs), which was further augmented by GR gel -induced macrophage M2-phonotype polarization and the effective M2 macrophage-BMSC crosstalk. The repair of critical-size skull bone defect in rat indicated a superior efficacy of PCL/nHA@GR gel implant on bone regeneration and osseointegration, with an average bone area of 83.3% throughout the defect location at 12 weeks post treatment. Furthermore, the osteo-immunomodulatory GR gel induced a reparative microenvironment similar with that in normal cranium, as characterized by an increased percentage of anti-inflammatory M2 macrophages and osteoblasts, and high-level vascularization. Collectively, the composite scaffold developed here with macrophage polarization-mediated osteo-immunomodulation may represent a promising implant for expediting in situ bone regeneration by providing biochemical and osteoinductive cues at the injured tissue.